Effects of root exudates on the sorption of polycyclic aromatic hydrocarbons onto biochar. Issue 1 (1st January 2019) - Li, Xiaona; Song, Yang; Bian, Yongrong; Wang, Fang; Gu, Chenggang; Yang, Xinglun; Jiang, Xin
ABSTRACT: The effect of oxalic acid on phenanthrene sorption was varied from that on pyrene sorption. 1.0 mg L -1 of oxalic acid inhibited phenanthrene sorption, whereas 20, 50 and 100 mg L -1 of oxalic acid enhanced the sorption. However, pyrene sorption onto biochar was all inhibited among different concentrations of oxalic acid. New functional groups and increased polarity were observed in the biochar coexisted with oxalic acid, moreover, a high concentration of oxalic acid led to an increased specific surface area of the biochar. These changed factors contributed to biochar sorption to phenanthrene, which was dominated by surface adsorption. Weakened aromaticity and increased release of dissolved organic carbon from biochar may have been the main reason for inhibited pyrene sorption onto biochar by oxalic acid. Therefore, this study suggested that root exudates could greatly influence the sorption behavior of biochar towards PAHs in soil rhizosphere, which deserves attention in agricultural systems. ABSTRACT: